Are skin disorders related to work strain in hospital workers? A cross-sectional study - Magnavita Anna M; Heponiemi Tarja; Elovainio Marko; Magnavita Nicola; Bergamaschi Antonio (BMC, 2011)
Abstract Background To evaluate whether occupational stress factors (high demands, low control, low social support, strain, and iso-strain) are associated with skin disorders in hospital workers and whether psychological problems, such as anxiety and depression, act as potential mechanisms through which occupational stress factors are associated with skin disorders. Methods 1,744 hospital workers were invited to answer a questionnaire concerning the occurrence of skin disorders and psychosocial factors at work. The abbreviated Italian version of the Demand/Control model (Karasek) was used to assess perceived work strain, while the Goldberg scales were used to assess anxiety and depression. Analyses were adjusted for age, gender, occupation, latex glove use and history of atopy. Results Of the participants, 25% reported hand dermatitis in the previous 12 months and 35% had been affected by skin disorders in other parts of the body. High job demands (OR = 1.09 CI95% 1.05-1.14), low social support (OR = 0.90, CI95% 0.87-0.93), high strain (OR = 1.54 CI95% 1.20-1.98) and high iso-strain (1.66 CI95% 1.27-2.19) were all associated with a higher prevalence of reported hand skin disorders. Both depression (OR = 2.50 CI95% 1.99-3.14) and anxiety (OR = 2.29 CI95% 1.81-2.89) were associated with higher risk of hand skin disorders. The same pattern was observed for dermatological complaints in other parts of the body. Only a slight reduction in the association between occupational stress variables and skin disorders was observed after including depression and anxiety in the model. Conclusions Job stress plays a significant role in triggering skin disorders among hospital workers and psychological problems do not appear to be the mechanism behind this association. Occupational health education and training should focus on reducing job demands and occupational stress in order to prevent skin problems among hospital workers.